Estimating the Basal Heave Stability of Narrow Braced Excavations - Taoli Xiao; Yanlu Yang; Hua Cai; Shaoxin Yan; Fang Cao (Shock and Vibration)
Engineering practices indicate that narrow braced excavation exhibits a clear size effect. However, the slip circle method in the design codes fails to consider the effect of excavation width on basal heave stability, causing waste for narrow excavation. In this paper, numerical simulation for basal heave failure of excavation with different widths was performed by FEM with SSRT (shear strength reduction technique). The results revealed that the failure mechanism of narrow excavation is different from the complete slip circle mode. In addition, the safety factor decreases increasingly slowly as the excavation widens and stabilizes when approaching the critical width. Subsequently, the corresponding computation model was presented, and an improved SCM (slip circle method) was further developed. Finally, the engineering case illustrated that it can effectively optimize the design, which exhibits clear superiority.